ANALISIS PENERAPAN PEMBELAJARAN DEEP LEARNING TERHADAP PENINGKATAN KATERAMPILAN BERPIKIR KRITIS SISWA PADA MATERI SKALA DI KELAS VI MI AL-FALAH - Alfiyatin, Yuliana (STIT Al-Ibrohimy Bangkalan, 2025)
The results of the interviews revealed that sixth-grade students at MI Al-Falah Dakiring Socah Bangkalansaat are currently experiencing difficulties in learning because they are unmotivated and do not pay attention to the teacher's explanations. As a result, many students are unable to develop critical thinking skills and often give perfunctory answers to the exercises given by the teacher. They also lack in-depth analysis of the steps needed to solve the problems given. Deep learning, which is pedagogical learning to meet the needs of today's education. Deep learning is learning that focuses on a comprehensive understanding of concepts, meaningful information management, and the ability of students to relate the knowledge they have acquired to real life, as well as to think critically, reflectively, and creatively in problem solving. This research method is field research that adopts a qualitative approach. Field research includes types of research that require researchers to go directly to the research location and interact directly with the local community. In this study, researchers can directly experience the phenomena that arise in the field and gain a comprehensive and clear understanding of the situation and conditions at the research location. The analysis shows that there are changes in students before and after using deep learning. Among other things, students become more active in discussions with their classmates and group members, actively ask questions, actively search for data or information through learning resources, and analyze each question by trying to answer based on analysis and data. Students are more confident in expressing their opinions, challenging their peers' opinions based on data and analysis, and willing to collaborate to find solutions to the questions and problems they encounter. This indicates an improvement in students' critical thinking skills through the use of deep learning in the scale material in the sixth grade at MI Al-Falah Dakiring Socah Bangkalan. This certainly has a positive impact, enabling learning objectives to be achieved. Given several obstacles in the learning process, as a researcher and classroom teacher, I have carefully prepared learning scenarios before the lessons begin so that the efforts that have been planned can minimize the obstacles encountered during the learning process, thereby ensuring that the learning objectives are achieved to the fullest extent possible. Keywords: Deep learning, critical thinking skills